About uniform distribution of four-dimensional torus - Kryžienė, Birutė; Misevičius, Gintautas (Lietuvos matematikos rinkinys, 2002)
Results on the uniform distribution of ergodic endomorphisms on the four-dimensional torus are obtained. They extend previous results [1] for the case when the characteristic polynomial of matrix V may be reducible.